Porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material as well as preparation method and application thereof

By using porous carbon fiber to support black phosphorus/nitrogen doped carbon composite in sodium ion batteries, the volume effect of black phosphorus in sodium ion batteries and the problem of lonely electron instability in phosphorus atoms is solved, high specific capacity, excellent rate performance and cyclic reversibility are achieved, and the battery energy density is improved.

CN119560522AActive Publication Date: 2025-03-04HEFEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411553675.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-03
Publication Date
2025-03-04
Estimated Expiration
2044-11-03

AI Technical Summary

Technical Problem

The volume effect of black phosphorus in sodium ion batteries and the unstability of the electrons in phosphorus atoms leads to slow kinetics of electrochemical reactions, poor cycle reversibility and extremely fast capacity attenuation.

Method used

Porous carbon fibers are used to support black phosphorus/nitrogen doped carbon composites, and nitrogen-doped porous carbon fiber conductive frames are prepared through metal-assisted chemical etching technology, and red phosphorus is converted into black phosphorus through solvent thermal and domain-limited growth strategies. In situ domain-limited growth is grown in the pores of nitrogen-doped carbon-coated porous carbon fiber frames to form high-performance phosphorus/carbon heterostructure composites.

Benefits of technology

High specific capacity, excellent rate performance and cycle reversibility are achieved, and additional conductive agents, binders and current collectors are avoided, and the battery energy density is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560522A_ABST
    Figure CN119560522A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material as well as a preparation method and application thereof, and belongs to the field of new energy materials and devices. A nitrogen-doped carbon-coated porous carbon fiber conductive frame is prepared by using a metal-assisted chemical etching technology, then red phosphorus is converted into black phosphorus by adopting a solvothermal and confinement growth strategy, and the black phosphorus grows in a pore channel of the nitrogen-doped carbon-coated porous carbon fiber frame in an in-situ confinement manner, so that the high-performance self-supporting phosphorus / carbon heterostructure electrode material is constructed and obtained. The three-dimensional nitrogen-doped carbon-coated porous carbon fiber conductive framework realizes high-speed electron / ion transmission and limits the expansion of the electrode structure; abundant nitrogen doping defects are beneficial to abundant reaction active sites and enhancement of reaction kinetics; the in-situ formed phosphorus / carbon heterogeneous interface can promote electron transfer and ion diffusion, stabilize the electrode structure and realize stable, rapid and reversible sodium storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy materials and devices, and specifically relates to a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material and a preparation method and application thereof. Background Art

[0002] New secondary energy storage technologies are developing rapidly. Sodium-ion batteries have the characteristics of abundant resources, low solvation effect and high safety, and may become the new main force of next-generation energy storage batteries in the future. However, the larger radius of sodium ions This leads to slow ion diffusion, electrode structure damage and poor stability of the solid electrolyte interface (SEI); the higher redox potential (-2.71V) reduces its open circuit voltage and energy density. The key to ensuring that sodium ion batteries exhibit excellent rate performance, cycle stability and high energy density is to develop electrode materials with fast electrochemical reaction kinetics, robust structure, high reversible capacity and low redox potential through electrode component and structural design.

[0003] Phosphorus has a high theoretical capacity (2596 mAh g -1 ), low charge and discharge potential (~0.2V / ~0.5V vs.Na + / Na) and other characteristics have attracted much attention, and it is expected to significantly improve the energy density of sodium-ion batteries when used as negative electrode materials. Phosphorus exists in three allotropes: white phosphorus, red phosphorus and black phosphorus, and their properties are different. Among them, white phosphorus is highly toxic and flammable, and is not suitable as an electrode material; red phosphorus is low-cost and non-toxic, and has been widely studied as a negative electrode for sodium-ion batteries. However, red phosphorus has a low intrinsic conductivity (10 -14 S m -1 ) and significant volume effect, resulting in slow electrochemical reaction kinetics, poor cycle reversibility and extremely rapid capacity decay. The new nanomaterial black phosphorus has a two-dimensional folded layered structure and has high conductivity (300S m -1 ), high carrier mobility, good thermal stability and high anisotropy, making it an ideal negative electrode material for sodium ion batteries. Single block black phosphorus has serious volume expansion and large voltage hysteresis during the sodium insertion / extraction process. Nano-sizing black phosphorus can alleviate the volume effect, shorten the ion diffusion distance and enhance the reaction activity. However, the self-aggregation effect of nanoparticles leads to a decrease in the electrode / electrolyte contact area, an increase in the interface resistance, and slow ion diffusion kinetics. Anchoring the nanoparticles in conductive carbon with a hierarchical pore structure can effectively limit their self-aggregation through spatial confinement, thereby enriching the reaction interface. In addition, the lone pair electrons in the phosphorus atoms make black phosphorus extremely sensitive to water and oxygen in the environment and have poor cyclic stability. When it is composited with conductive porous carbon, a phosphorus / carbon heterogeneous interface is formed in situ through bonding, which can promote electron transfer and sodium ion diffusion and stabilize the electrode structure.

[0004] Innovating the traditional electrode structure, adopting the integrated design of electrode materials and current collectors, and developing new self-supporting sodium-ion battery negative electrode materials have become a new hot spot in sodium-ion battery research. Through the optimization design of the microstructure of the electrode material, the self-supporting hierarchical porous carbon network and the alloy-type black phosphorus negative electrode material are composited to construct a high-performance self-supporting electrode material with a phosphorus / carbon heterostructure. When hierarchical porous carbon is used as the conductive support skeleton, fast electron transport and excellent ion diffusion kinetics can be achieved, while effectively limiting the self-aggregation effect of nanomaterials and the volume effect during the cycle; the abundant pore structure gives it a large specific surface area, which can enhance the infiltration of the electrolyte into the active components; heteroatom doping introduces defect structures, which can enrich the reaction active sites and enhance the reaction kinetics, thereby effectively improving the electrochemical performance of the electrode material. Summary of the invention

[0005] The purpose of the present invention is to provide a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material and a preparation method thereof to address the serious volume effect of black phosphorus and the instability of lone pair electrons in phosphorus atoms. When the self-supporting composite material is used as a negative electrode material for sodium ion batteries, it exhibits high specific capacity, excellent rate performance and cycle reversibility.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material, in which rod-shaped tiny black phosphorus nanoparticles are dispersed in the nitrogen-doped carbon coated porous carbon fiber conductive framework to form a porous carbon fiber supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material. The area loading of the active material (BP@NC) in the composite material is 1.8-2.0 mg cm -2 The mass ratio of black phosphorus in the composite material is 30-50%.

[0008] A method for preparing a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material, firstly using metal-assisted chemical etching technology to prepare a nitrogen-doped carbon-coated porous carbon fiber conductive framework, then using solvent thermal and confined growth strategies to convert red phosphorus into black phosphorus and in situ confined growth in the pores of the nitrogen-doped carbon-coated porous carbon fiber framework, to construct a high-performance phosphorus / carbon heterostructure composite material, namely, a porous carbon fiber supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material.

[0009] As a preferred technical solution of the present invention, the specific steps of the preparation method of the porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material are as follows:

[0010] (1) ultrasonically cleaning a commercial carbon fiber cloth with acetone, ethanol and deionized water in sequence, and then drying it; electrochemically depositing nickel hydroxide on the carbon fiber cloth using a three-electrode system with a metal platinum sheet as a counter electrode, the carbon fiber cloth as a working electrode, and Ag / AgCl as a reference electrode, and drying it for later use;

[0011] (2) Weigh a certain amount of polyacrylonitrile and polyvinyl pyrrolidone and dissolve them in an appropriate amount of N,N-dimethylformamide solvent, and continue stirring for a period of time to obtain a viscous solution;

[0012] (3) fully immersing the carbon fiber cloth with nickel hydroxide loaded on the surface obtained in step (1) in the above viscous solution for 5 minutes, taking it out and drying it; then calcining it at high temperature in an argon / hydrogen mixed atmosphere; finally, washing it in a hydrochloric acid solution to remove nickel particles, washing it, and drying it to obtain a nitrogen-doped carbon-coated porous carbon fiber (NC / PCF) composite material;

[0013] (4) A certain amount of purified red phosphorus is dissolved in an appropriate amount of ethylenediamine solution, and then the nitrogen-doped carbon-coated porous carbon fiber composite material is fully immersed in the mixed solution, and then transferred into a high-pressure reactor for solvent thermal reaction; finally, the product is washed and dried to obtain a porous carbon fiber supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material.

[0014] As a further preferred technical solution of the present invention, in the preparation method:

[0015] In step (1), during the electrochemical deposition of nickel hydroxide, 1 mol L -1 Nickel nitrate (Ni(NO 3 ) 2 ) and 0.1 mol L -1 Sodium nitrate (NaNO 3 ) is the electrolyte, the volume ratio of nickel nitrate solution to sodium nitrate solution is 1:1; the current density is 7-9 mA cm -2 , the deposition time is 10 to 30 minutes.

[0016] In step (2), the mass volume concentration of polyacrylonitrile in the viscous solution is 0.08 g mL -1 The mass ratio of polyacrylonitrile and polyvinyl pyrrolidone is 1:1~3.

[0017] In step (3), the high temperature calcination temperature is 800-1000°C, the calcination time is 1-3h, and the heating rate is 5-10°C min -1 .

[0018] In step (4), the specific steps of red phosphorus purification are: first, weigh 3.0 g of commercial red phosphorus and disperse it in 80 mL of deionized water, then perform hydrothermal purification in a high-pressure reactor at a hydrothermal temperature of 200° C. for 12 h, and finally centrifuge the product, wash with ethanol and dry it to obtain purified red phosphorus.

[0019] In step (4), the solvent thermal reaction temperature is 180-200° C. and the time is 10-12 hours.

[0020] The porous carbon fiber supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material prepared by the present invention is applied as a negative electrode material in a sodium ion battery, avoiding the use of additional conductive agents, binders and current collectors, thereby improving the battery energy density.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] 1) The present invention uses nitrogen-doped carbon-coated porous carbon fibers with high mechanical strength and stable structure as a conductive support skeleton to accelerate electron / ion transmission and limit electrode volume expansion; the three-dimensional hierarchical pore structure gives the composite material a high specific surface area, which is beneficial to enhance the infiltration of the electrolyte into the active material; nitrogen-doped defects are beneficial to enrich the reaction active sites and enhance the reaction kinetics; the diffusely distributed black phosphorus particles can effectively shorten the ion diffusion distance; the in-situ formed phosphorus / carbon heterogeneous interface can promote electron transfer and sodium ion diffusion, stabilize the electrode structure, and achieve stable and rapid reversible sodium storage.

[0023] 2) The sodium ion battery self-supporting negative electrode material (BP@NC / PCF) prepared in the present invention does not require the use of current collectors, conductive agents and binders when assembling batteries. The manufacturing process is simple, low-cost, and environmentally friendly, which is conducive to industrial promotion and is of great significance to the development of self-supporting negative electrode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD curve of the nitrogen-doped carbon-coated porous carbon fiber composite material (NC / PCF) in Example 1.

[0025] Figure 2 XRD curves of (a) black phosphorus and (b) porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF) in Example 1.

[0026] Figure 3 (a) low and (b) high magnification SEM morphology images of the nitrogen-doped carbon-coated porous carbon fiber composite material (NC / PCF) in Example 1.

[0027] Figure 4(a) SEM and (b) TEM morphology images of the porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF) in Example 1.

[0028] Figure 5 (a) N of the porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF) in Example 1 2 (a) Adsorption-desorption isotherm and (b) DFT pore size distribution diagram (the inset is the curve diagram of pore size distribution ≤ 2 nm).

[0029] Figure 6 (a) XPS full spectrum and (b) C 1s, (c) N 1s, and (d) high-resolution spectra of P 2p elements of the porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF) in Example 1.

[0030] Figure 7 The sodium ion half-cell assembled based on the BP@NC / PCF electrode material in Example 1 was charged at 100 mA g -1 Lower cycle performance test results.

[0031] Figure 8 The results of the rate performance test of the sodium ion half-cell assembled based on the BP@NC / PCF electrode material in Example 1.

[0032] Fig. 9 The test results of the cycle performance of the sodium ion full battery assembled based on the BP@NC / PCF negative electrode material in Example 1 at 0.5C.

[0033] Fig.10 The results of the rate performance test of the sodium ion full battery assembled based on the BP@NC / PCF negative electrode material in Example 1.

[0034] Fig.11 The sodium ion half-cell assembled based on NC / PCF electrode material in Comparative Example 1 was -1 Lower cycle performance test results.

[0035] Fig.12 These are the rate performance test results of the sodium ion half-cell assembled based on NC / PCF electrode materials in Comparative Example 1. DETAILED DESCRIPTION

[0036] The porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material provided by the present invention and its preparation method and application are further described in detail below in conjunction with the embodiments and drawings.

[0037] Example 1

[0038] The present embodiment provides a method for preparing a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material. First, a nitrogen-doped carbon-coated porous carbon fiber conductive framework is prepared by metal-assisted chemical etching technology. Then, a solvent thermal and confined growth strategy is used to convert red phosphorus into black phosphorus and in situ confined growth is carried out in the pores of the nitrogen-doped carbon-coated porous carbon fiber framework to construct a high-performance phosphorus / carbon heterostructure composite material for sodium ion battery negative electrode material.

[0039] The specific steps include:

[0040] (1) Commercial carbon fiber cloth was ultrasonically cleaned with acetone, ethanol and deionized water for 10 to 30 min, and then dried at 60°C for 8 h. A three-electrode system was used to electrochemically deposit nickel hydroxide on the carbon fiber cloth, using a platinum sheet as the counter electrode, the carbon fiber cloth as the working electrode, and Ag / AgCl as the reference electrode. During the electrochemical deposition process, 1 mol L -1 Nickel nitrate (Ni(NO 3 ) 2 ) and 0.1 mol L -1 Sodium nitrate (NaNO 3 ) (volume ratio is 1:1) as the electrolyte, and the current density is 8 mA cm -2 The deposition time was 20 min; the prepared sample was then dried at 60°C for 12 h for later use.

[0041] (2) Weigh polyacrylonitrile and polyvinyl pyrrolidone in a mass ratio of 1:2 and dissolve them in N,N-dimethylformamide solvent. Stir continuously at 60°C for 12 hours to obtain a viscous solution. The mass volume concentration of polyacrylonitrile in this solution is 0.08 g / mL -1 .

[0042] (3) The carbon fiber cloth with nickel hydroxide loaded on the surface was fully immersed in the above viscous solution, taken out after 5 minutes, and dried at 60°C for 8 hours; then, it was calcined at a high temperature in an argon / hydrogen mixed atmosphere with a volume ratio of 5:1, the calcination temperature was 900°C, the calcination time was 2 hours, and the heating rate was 10°C min -1 ; Finally, place it in 3 mol L -1 The nickel particles were removed by pickling in a hydrochloric acid solution at 80°C for 5 h, and then the composite was washed and dried to obtain a nitrogen-doped carbon-coated porous carbon fiber (NC / PCF) composite material.

[0043] (4) The specific steps of red phosphorus purification are as follows: first, 3.0 g of commercial red phosphorus is weighed and dispersed in 80 mL of deionized water, followed by hydrothermal purification in a high-pressure reactor at a hydrothermal temperature of 200 °C for 12 h. Finally, the product is centrifuged, washed with ethanol, and dried to obtain purified red phosphorus.

[0044] (5) 0.3 g of purified red phosphorus was dissolved in 50 mL of ethylenediamine solution, and then the NC / PCF composite material was fully immersed in the mixed solution and then transferred into a high-pressure reactor for solvothermal reaction at a solvothermal temperature of 200 °C for 12 h. Finally, the product was washed and dried to obtain a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF). When the BP@NC / PCF composite material was used as a self-supporting negative electrode material for sodium ion batteries, the area loading of the active material was 1.8 mg cm -2 The mass ratio of black phosphorus in BP@NC / PCF composite material is 47.3%.

[0045] See also Figure 1 , which is the XRD curve of the nitrogen-doped carbon-coated porous carbon fiber composite material (NC / PCF) prepared in this embodiment. As can be seen from the figure, after metal-assisted chemical etching and pickling treatment, the NC / PCF composite material can be obtained, and the diffraction peaks at 25.7° and 43.8° correspond to the (002) and (100) crystal planes of graphitized carbon, respectively. Combined with the SEM morphology of the NC / PCF composite material ( Figure 3 ) It can be seen that the hierarchical pores in the composite material present a cross-linked interconnected structure, which can provide convenient channels for electron migration and ion diffusion, and at the same time can significantly expand the specific surface area of ​​the composite material, which is beneficial to enhance the electrolyte penetration and improve the reaction activity of the active material; in addition, the pore structure has a good pore confinement effect.

[0046] See also Figure 2 , which shows the XRD curves of black phosphorus and porous carbon fiber supported black phosphorus / nitrogen-doped carbon composites (BP@NC / PCF). Figure 2 a It can be seen that 17.4°, 27.4°, 35.3°, 35.5°, 41.4° and 57.5° correspond to the (020), (021), (040), (111), (041) and (151) crystal planes of BP, respectively (PDF#76-1967); In addition, during the solvothermal reaction of ethylenediamine, since two P atoms in a unit cell are replaced by vacancies or H atoms, the crystal structure along the c-axis direction is dislocated or periodically distorted, and the lattice spacing is changed from Increase to As a result, obvious diffraction peaks appear at 10.3° and 31.1°. Figure 2 b It can be seen that NC / PCF was placed as a conductive support skeleton in an ethylenediamine solution containing red phosphorus, and the BP@NC / PCF composite material was prepared by solvent thermal reaction. In the XRD spectrum of BP@NC / PCF, the diffraction peaks of BP at 10.3° and 17.4° can be observed, while the diffraction peaks at other positions are obscured by the high-intensity diffraction peaks of the graphitized carbon (002) crystal plane and are not easy to be observed. Combined with the SEM morphology of the BP@NC / PCF composite material ( Figure 4 a) It can be seen that tiny black phosphorus nanoparticles cannot be directly observed in the pores. The main reason is that the confinement effect of the three-dimensional hierarchical pore structure in the NC / PCF composite material can inhibit the continuous growth of black phosphorus nanoparticles. Figure 4 b) It can be seen that the rod-shaped black phosphorus nanoparticles are about 8 nm in length, and the porous carbon tightly wraps the black phosphorus nanoparticles, which can effectively alleviate the large stress and strain of black phosphorus during the electrochemical reaction and enhance the stability of the electrode structure.

[0047] See also Figure 5 , the figure shows the (a) N 2 (a) Adsorption-desorption isotherm and (b) DFT pore size distribution diagram (the inset is the curve diagram of pore size distribution ≤ 2 nm). 2 The adsorption-desorption isotherm curve contains obvious hysteresis loops, which is due to the capillary condensation phenomenon caused by the presence of rich mesoporous structure, proving that the material contains rich mesoporous structure. The specific surface area of ​​BP@NC / PCF composite material calculated by Brunauer-Emmett-Teller (BET) method is 435.85m 2 g -1 , the pore volume is 0.623cm 3 g -1 , the pore size distribution range is 0.3~290nm. It can be seen that the larger specific surface area in BP@NC / PCF composite material is conducive to improving the infiltration of electrolyte into active components, and also provides abundant channels for sodium ion diffusion. The hierarchical pore structure can provide more reactive sites and help alleviate the volume effect of black phosphorus nanoparticles. Through the spatial confinement effect of porous carbon, it is conducive to the formation of phosphorus / carbon heterogeneous interface, promote electron transfer and ion diffusion, and stabilize the electrode structure.

[0048] See also Figure 6, the figure shows the (a) XPS full spectrum and (b) C 1s, (c) N 1s, (d) P 2p high-resolution spectra of the porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF). From the XPS full spectrum, it can be seen that the BP@NC / PCF composite material contains four elements: C, O, N and P. In the C1s high-resolution spectrum, the characteristic peaks with binding energies of 284.0, 284.7, 285.8 and 288.2 eV correspond to the CP bond, CC / C=C bond, CO / C=N bond and C=O bond, respectively; in the N1s high-resolution spectrum, there are characteristic peaks corresponding to the pyridine-N bond (399.1 eV), pyrrole-N bond (400.3 eV) and graphite-N bond (401.5 eV); in the P2p high-resolution spectrum, the binding energies of 130.8 and 131.4 correspond to the P 2p of the phosphorus element. 3 / 2 and P 2p 1 / 2 The characteristic peaks with binding energies of 133.6 and 1134.5 eV correspond to POC bonds and PC bonds, respectively. XPS analysis results show that the BP@NC / PCF composite material contains phosphorus and nitrogen-doped carbon, which serve as active substances in the electrochemical reaction of sodium-ion batteries and provide capacity for self-supporting sodium-ion battery electrode materials. In addition, black phosphorus forms strong chemical bonds with PC during heterogeneous nucleation and growth in hierarchical channels, which can stabilize the lone pairs of electrons on the surface of black phosphorus and improve its stability.

[0049] The BP@NC / PCF self-supporting electrode material prepared in this example was used as the working electrode, the sodium sheet was used as the counter electrode, the GF / D glass microfiber membrane was used as the diaphragm, and the sodium perchlorate NaClO was used as the 4 As the solute, ethylene carbonate EC and dimethyl carbonate DMC with a volume ratio of 1:1 were used as solvents, and the concentration was 1 mol L -1 The solution was prepared by adding 5 wt % of fluoroethylene carbonate FEC as an electrolyte; finally, a 2032-type button-type sodium ion half-cell was assembled and a charge and discharge test was performed, and the test voltage window was 0.01-2V.

[0050] See also Figure 7 This figure shows the sodium ion half-cell assembled based on BP@NC / PCF electrode material in this embodiment at 100mA g -1 Cyclic performance test results of BP@NC / PCF||Na half-cell at 100mA g -1 The initial charge and discharge specific capacities were 721 and 1015 mAh g -1 The initial coulombic efficiency is 70.9%. The main reasons for the low initial coulombic efficiency are: (1) side reactions between inactive components in the electrolyte and sodium metal; (2) the electrolyte decomposes and forms a solid electrolyte interface (SEI) on the electrode surface; (3) some Na +Irreversible embedding occurs in the host material. During the first 40 cycles, the charge and discharge capacity shows an upward trend because the electrolyte continues to penetrate and infiltrate, and the electrode active material is in a state of continuous activation. After 150 cycles, the capacity can reach 890mAh g -1 The coulombic efficiency is 99.9%, compared with the reversible capacity at the 40th cycle (926 mAh g -1 ), the capacity retention rate is 96.1%, showing excellent cycle stability.

[0051] See also Figure 8 , which is the rate performance test result of the sodium ion half-cell assembled based on the BP@NC / PCF electrode material in Example 1. As shown in the figure, the current density is 0.1~2.0A g -1 The range of the step-wise increase is 0.1, 0.2, 0.4, 0.6, 0.8, 1.0 and 2.0 A g -1 The average capacities at 100 mAh g were 989, 864, 708, 606, 507, 415 and 304 mAh g -1 When the current density returns to 0.1A g -1 When the capacity is still up to 926mAh g -1 , showing excellent rate performance.

[0052] See also Fig. 9 , which is the test result of the cycle performance of the sodium ion full battery assembled based on the BP@NC / PCF negative electrode material in Example 1 at 0.5C. As shown in the figure, at a current density of 0.5C, the initial capacity of the full battery in this example at 0.5C is 128mAh g -1 After 200 cycles, the battery capacity is 99 mAh g -1 , showing good cycle stability.

[0053] See also Fig.10 , which is the rate performance test result of the sodium ion full battery assembled based on the BP@NC / PCF negative electrode material in Example 1. As shown in the figure, the current density increases stepwise in the range of 0.2-3.0C. The average capacities of the full battery in this example at 0.2, 0.5, 0.8, 1.0, 1.5, 2.0 and 3.0C are 130, 120, 115, 109, 104, 100 and 91 mAh g, respectively. -1 When the current density returned to 0.2C, the capacity reached 116 mAh g -1 , showing good rate performance.

[0054] The above battery performance test results show that a porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material (BP@NC / PCF) provided by the present invention has good electrochemical performance, which is mainly attributed to the three-dimensional conductive NC / PCF framework in this composite material that accelerates electron / ion transmission and limits electrode volume expansion; rich nitrogen-doped defects are conducive to abundant reaction active sites and enhanced reaction kinetics; the in-situ formed phosphorus / carbon heterogeneous interface promotes electron transfer and sodium ion diffusion, stabilizes the electrode structure, and realizes stable and rapid reversible sodium storage.

[0055] Comparative Example 1

[0056] In order to compare and illustrate the effect of the black phosphorus nanoparticles, an active substance in the BP@NC / PCF composite material provided by the present invention, on the electrochemical properties of the electrode material, the method for preparing the negative electrode material for a sodium ion battery in this comparative example is basically the same as that in Example 1, except that the red phosphorus purification step (4) and the solvent thermal reaction step (5) are removed to prepare nitrogen-doped carbon-coated porous carbon fibers (NC / PCF) as a self-supporting negative electrode material for a sodium ion battery.

[0057] The NC / PCF electrode material prepared in this comparative example is used as the working electrode, the sodium sheet is used as the counter electrode; the GF / D glass microfiber membrane is used as the diaphragm; sodium perchlorate NaClO 4 As the solute, ethylene carbonate EC and dimethyl carbonate DMC with a volume ratio of 1:1 were used as solvents, and the concentration was 1 mol L -1 A solution was prepared and 5 wt% of fluoroethylene carbonate FEC was added as an electrolyte; a 2032 button-type sodium ion half-cell was assembled and a charge and discharge test was performed, and the test voltage window was 0.01-2V.

[0058] See also Fig.11 , which shows the sodium ion half-cell assembled based on NC / PCF electrode material in Comparative Example 1 at 100 mA g -1 Cyclic performance test results of NC / PCF||Na half-cell at 100mA g -1 The initial charge and discharge specific capacities were 90 and 151 mAh g -1 The initial coulombic efficiency is 59.6%; after 150 cycles, the capacity is 88 mAh g -1 The reversible capacity of NC / PCF electrode material is significantly lower than that of BP@NC / PCF electrode material. The main reason is that Na +In the NC / PCF composite material, only adsorption / intercalation reaction occurs, and the initial coulombic efficiency is also low, which further reduces the capacity output during subsequent cycles. However, there are intercalation-alloying and adsorption / intercalation reactions in the BP@NC / PCF electrode material, which can provide a higher reversible capacity. However, it is worth noting that the NC / PCF composite material has a low capacity decay rate and excellent cycle stability due to its good conductivity.

[0059] See also Fig.12 , which is the rate performance test result of the sodium ion half-cell assembled based on the NC / PCF electrode material in Comparative Example 1. NC / PCF||Na at 0.1, 0.2, 0.4, 0.6, 0.8, 1.0 and 2.0A g -1 The average capacities at 103, 95, 89, 85, 81, 75 and 68 mAh g -1 When the current density returns to 0.1A g -1 The reversible capacity is 94 mAh g -1 , the rate performance is significantly lower than that of the negative electrode material in Example 1.

[0060] The half-cell performance test results in Comparative Example 1 show that when the BP@NC / PCF composite material is used as the negative electrode material of the sodium ion battery, the active substance black phosphorus based on the reversible embedding-alloying reaction can provide a higher reversible capacity for the electrode material, while the capacity provided by the porous carbon based on the adsorption / embedding reaction is limited.

[0061] Since the performance test results of the sodium ion half-cell assembled based on NC / PCF electrode materials were inferior to those of BP@NC / PCF electrode materials, performance tests were not conducted on the full cell assembled based on BP@NC / PCF negative electrode materials.

[0062] Example 2

[0063] The preparation method of this embodiment is the same as that of embodiment 1, except that the current density during electrochemical deposition in step (1) is reduced to 7 mA cm -2 , other conditions remain unchanged. Compared with Example 1, the current density during electrochemical deposition in this embodiment is reduced, resulting in a decrease in the content of nickel hydroxide deposited in the carbon fiber cloth, which is not conducive to the formation of a hierarchical porous carbon network during high-temperature reduction and etching, and reduces the electrochemical performance of the BP@NC / PCF electrode material. In the half-cell test, the current density is 100 mA g -1 When the initial charge and discharge specific capacities of the electrodes are 617 and 913 mAh g -1 The initial coulombic efficiency is about 67.5%; after 150 cycles, the reversible capacity is 523 mAh g -1The capacity retention rate is 84.7%, which is significantly lower than the electrode material in Example 1. In addition, the electrochemical performance of the full battery is also reduced.

[0064] Example 3

[0065] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of high-temperature reduction and etching in step (3) is reduced to 800°C, and other conditions remain unchanged. Compared with embodiment 1, the temperature of high-temperature reduction and etching in this embodiment is reduced, resulting in insufficient etching of nitrogen-doped carbon-coated carbon fibers, and failure to form a porous carbon network with a confining effect, which limits the black phosphorus content in the NC / PCF composite material and leads to a decrease in the electrochemical performance of the BP@NC / PCF electrode material. In the half-cell test, the current density is 100mA g -1 When the initial charge and discharge specific capacities of the electrodes are 481 and 783 mAh g -1 The initial coulombic efficiency is about 61.4%; after 150 cycles, the reversible capacity is only 324 mAh g -1 The capacity retention rate is 67.3%, which is significantly lower than the electrode material in Example 1. In addition, the electrochemical performance of the full battery is also reduced.

[0066] Example 4

[0067] The preparation method of this embodiment is the same as that of embodiment 1, except that unpurified red phosphorus is used for the solvothermal reaction in step (4), and other conditions remain unchanged. Compared with embodiment 1, the BP@NC / PCF composite material prepared by using unpurified red phosphorus in this embodiment not only contains residual red phosphorus, but also produces other impurities, which is not conducive to the performance of the BP@NC / PCF electrode material. In the half-cell test, the current density is 100mA g -1 When the initial charge and discharge specific capacities of the electrodes are 354 and 618 mAh g -1 The initial coulombic efficiency is about 57.2%; after 150 cycles, the reversible capacity is only 207 mAh g -1 , the capacity retention rate is 58.4%, which is significantly lower than the electrode material in Example 1. In addition, the electrochemical performance of the full battery is also reduced.

[0068] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material, characterized in that: Tiny black phosphorus nanoparticles in the shape of rods are dispersed in the nitrogen-doped carbon-coated porous carbon fiber conductive framework to form a porous carbon fiber-supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material. The area loading of the active material (BP@NC) in the composite material is 1.8-2.0 mg cm -2 The mass ratio of black phosphorus in the composite material is 30-50%.

2. A method for preparing the porous carbon fiber supported black phosphorus / nitrogen-doped carbon composite material as claimed in claim 1, characterized in that: Firstly, a nitrogen-doped carbon-coated porous carbon fiber conductive framework was prepared by metal-assisted chemical etching technology. Then, solvothermal and confined growth strategies were adopted to convert red phosphorus into black phosphorus and in situ confined growth it in the pores of the nitrogen-doped carbon-coated porous carbon fiber framework to construct a high-performance phosphorus / carbon heterostructure composite material, namely, a porous carbon fiber supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material.

3. The preparation method according to claim 2, characterized in that: The specific steps are as follows: (1) ultrasonically cleaning a commercial carbon fiber cloth with acetone, ethanol and deionized water in sequence, and then drying it; electrochemically depositing nickel hydroxide on the carbon fiber cloth using a three-electrode system with a metal platinum sheet as a counter electrode, the carbon fiber cloth as a working electrode, and Ag / AgCl as a reference electrode, and drying it for later use; (2) Weigh a certain amount of polyacrylonitrile and polyvinyl pyrrolidone and dissolve them in an appropriate amount of N,N-dimethylformamide solvent, and continue stirring for a period of time to obtain a viscous solution; (3) fully immersing the carbon fiber cloth with nickel hydroxide loaded on the surface obtained in step (1) in the above viscous solution for 5 minutes, taking it out and drying it; then calcining it at high temperature in an argon / hydrogen mixed atmosphere; finally, washing it in a hydrochloric acid solution to remove nickel particles, washing it, and drying it to obtain a nitrogen-doped carbon-coated porous carbon fiber (NC / PCF) composite material; (4) A certain amount of purified red phosphorus is dissolved in an appropriate amount of ethylenediamine solution, and then the nitrogen-doped carbon-coated porous carbon fiber composite material is fully immersed in the mixed solution, and then transferred into a high-pressure reactor for solvent thermal reaction; finally, the product is washed and dried to obtain a porous carbon fiber supported black phosphorus / nitrogen-doped carbon (BP@NC / PCF) composite material.

4. The preparation method according to claim 3, characterized in that: In step (1), during the electrochemical deposition of nickel hydroxide, 1 mol L -1 Nickel nitrate (Ni(NO3)2) and 0.1 mol L -1 The mixed solution of sodium nitrate (NaNO3) is the electrolyte, the volume ratio of nickel nitrate solution to sodium nitrate solution is 1:1; the current density is 7-9 mA cm -2 , the deposition time is 10 to 30 minutes.

5. The preparation method according to claim 3, characterized in that: In step (2), the mass volume concentration of polyacrylonitrile in the viscous solution is 0.08 g mL -1 The mass ratio of polyacrylonitrile and polyvinyl pyrrolidone is 1:1~3.

6. The preparation method according to claim 3, characterized in that: In step (3), the high temperature calcination temperature is 800-1000°C, the calcination time is 1-3h, and the heating rate is 5-10°C min -1 .

7. The preparation method according to claim 3, characterized in that: In step (4), the specific steps of red phosphorus purification are: first weigh 3.0 g of commercial red phosphorus and disperse it in 80 mL of deionized water, then perform hydrothermal purification in a high-pressure reactor at a hydrothermal temperature of 200° C. for 12 h, and finally centrifuge the product, wash with ethanol and dry it to obtain purified red phosphorus.

8. The preparation method according to claim 3, characterized in that: In step (4), the solvent thermal reaction temperature is 180-200° C. and the time is 10-12 hours.

9. An application of the porous carbon fiber supported black phosphorus / nitrogen doped carbon (BP@NC / PCF) composite material as claimed in claim 1, characterized in that: The composite material is used as a negative electrode material in a sodium ion battery.

Citation Information

Patent Citations

  • Black phosphorus-based negative electrode material and preparation method thereof

    CN113437281A

  • Black phosphorus-carbon composite material as well as preparation method and application thereof

    CN115172711A

  • Preparation method of black phosphorus / nano carbon microsphere / nano carbon fiber composite negative electrode material

    CN115458733A

  • Phosphorus-based negative electrode, preparation method thereof and sodium ion battery

    CN117810371A

  • system for providing content of interactive personalized Pilates training

    KR1020240053178A